Hairspray [videorecording (Blu-Ray)] - Shankman, Adam; Travolta, John, 1954-; Pfeiffer, Michelle, 1957-; Walken, Christopher, 1943-; Bynes, Amanda, 1986-; Marsden, James, 1973-; Queen Latifah, 1970-; Snow, Brittany, 1986-; Efron, Zac; Janney, Allison; Blonsky, Nikki, 1988- (New Line Home Entertainment, 2007)
It's 1962 Baltimore and change is in the air. Tracy Turnblad, a plus-sized girl with big hair and big dreams, has only one passion in life - to dance on the 'The Corny Collins Show.' When her chance arrives, she grooves her way into instant stardom and the eyes of teen dream Link Larkin. But with the program's scheming stage manager against her, trend setting Tracy will need the help of her best friend Penny, her big hearted mom and sassy co-host Motormouth Maybell to show the world that all it takes to make a dream come true is a toe-tappin' beat.